Efficacy and Safety of "Sleeper Plate" in Temporary Hemiepiphysiodesis and the Observation of "Tethering". Issue 7 (20th August 2022) - Gerges, Mina; Messner, Juergen; Lim, Brittany; Chhina, Harpreet; Cooper, Anthony
Abstract : Background: Guided growth is commonly performed by placing an extraperiosteal 2-hole plate across the growth plate with one epiphyseal and one metaphyseal screw. Recent studies investigated the efficacy of the removal of the metaphyseal screw only (sleeper plate) after correction. They concluded the practice to be unnecessary as only 19% of patients showed recurrence of deformity. This study aims to examine the incidence of rebound and undesired bony in-growth of the plate (tethering) after metaphyseal screw removal only. Methods: In this retrospective case series, patient data on 144 plates inserted around the knee were obtained. Plates still in situ (n=69) at the time of study and full hardware removal (n=50) were excluded. The remaining 25 plates had only the metaphyseal screw removed after completed deformity correction. We analyzed the rate of tethering, rebound, and maintenance of correction in 2 age groups at latest follow (mean of 3.5 y). The Fisher exact test with Freeman-Halton extension was used to analyze categorical data and the Student t test for descriptive variables. Results: Twenty-five plates were identified as "sleeper plates" in our series. Thirteen plates (52%) maintained the achieved correction after a mean of 21 months (range: 4 to 39 mo), 9 plates (36%) required screw reinsertion due to rebound after a mean of 22 months (range: 12 to 48 mo) from screw removal, and 4 plates (16%) showed tethering with undesired continuation of guided growth after a mean of 14 months (range: 7 to 22 mo) from screw removal. Younger patients (<8 y at time of plate insertion) had higher rates of rebound and tethering ( P =0.0112, Fisher exact test). All tethering occurred in titanium plates, none occurred in steel plates. Conclusions: The sleeper plate is an acceptable treatment strategy for coronal deformities around the knee, however, tethering and rebound may occur, especially in younger patients. Titanium plates may increase the risk of tethering, however, further long-term follow-up is needed as there were only 6 steel plates versus 19 titanium in this study. We stress the importance of close postoperative follow-up to identify signs of tethering and rebound early to prevent over-correction. Level of Evidence: Level IV—retrospective case study.